TAX POLICY AS A KEY INSTRUMENT OF PUBLIC GOVERNANCE IN THE CONTEXT OF EUROPEAN INTEGRATION (Coordinates of Public Administration, 2026)
In the system of public governance and administration, tax policy plays a crucial role in ensuring the financial stability of the state by regulating taxes, stimulating business activity, and providing revenue for budgets at all levels. This paper examines the theoretical aspects of defining the essence and components of tax policy, as well as its classification and functioning within the budget process. The role of tax policy as a key factor in public governance in the context of European integration is substantiated. A comprehensive analysis of the dynamics and structure of tax revenues to the state and local budgets is carried out, identifying key factors that have led to shifts in fiscal flows. Strategic directions for improving tax policy are justified, along with prospects for the digitalization of tax administration (AI, Big Data, anti-shadow economy measures, and e-commerce regulation). A set of measures aimed at socially oriented redistribution and strengthening fiscal decentralization is proposed. The conducted research revealed the relationship between tax policy and the mechanism of forming the revenue side of the state and local budgets. It has been proven that tax revenues are the main source of filling the revenue part of budgets. Tax policy, in turn, is a direct factor that determines the mechanism for forming the revenue side of both state and local budgets. As a result of the analysis, it has been demonstrated that, despite the war, tax revenues remain the primary component of the budget system. The study made it possible to formulate strategic approaches and practical recommendations for optimizing the tax burden in order to improve Ukraine’s tax policy.